Socio-Cultural Shackles challenge Energy Efficiency Module Imparted to the Buildings of Iran - Hoorshenas, Razieh; amiri, arsalan; sadraie, Ali; yari, fahimeh; mahdavinejad, mohammadjavad (Advances in Social Sciences Research Journal, 2015)
Energy consumption range has been critically increased in the recent decades and prone to energy use decline specifically in buildings known as critical component to dispense carbon mitigation commitments. The deeply clear relationship between the Socio-Cultural Shackles and the pattern of energy efficiency in building industry is manifested according to studies done experimentally. In order to develop a viable program for improving the culture of energy thrift, it is very important to study and resolve the issue of the Socio-Cultural shackles and potentialities. Based on the research of Hellriegel Jackson and Slocum (1999), the community typically resist the improvement of domain attitudes and behaviors. The present paper investigates the Socio-Cultural shackles against the energy efficiency model imparted to building for the first time in Iran, therefore analysis of Socio-Cultural shackles helps us to find out a framework for correcting the attitudes to energy consumption trends in every community. Understanding the social and cultural impediments it would lead us to discover better the available social sources to mark up the energy efficiency dedicated to the building industry. In order to explore the social restraints discussed in the present article, the writer conducted three hundred interviews with consumers, architects, lawmakers and constructors. These interviews are based on the primitive literature of the social psychology in light of available issues encompass the energy efficiency commonly applicable in the building industry.